Danes’ class consciousness 1954 and 2015: Plus ça change, plus c’est la même chose - Stubager, Rune (Politica, 2017)
In recent years, the perception that citizens in Western countries like Denmark no longer see class differences in society – indeed that the concept of class has become irrelevant – has spread among researchers and the general public alike. On the basis of theories of class consciousness and the Danish National Election Study 2015, the article shows that this view is false. On the contrary, three out of four respondents in a Danish survey from 2014/15 see society as class divided and a considerable share espouses other elements of class consciousness. Furthermore – and in spite of profound societal changes in the intervening period – results from 2014/15 are, by and large, at the level of responses in a similar survey conducted in 1954.